Thermal Oxidation Process Improved Corrosion in Cobalt Chromium Molybdenum Alloys - Mas Ayu, Hassan; Rosdi, Daud; A., Shah; Mohd Faiz, M. Y.; Hazwan, H. M.; Salwani, Mohd Salleh; Siti Haryani, Tomadi; Reza, M. S. (IASE, 2017)
The corrosion phenomena are always give bad impact to any metal products including human implants. This is due to the corrosion impacts are harmful for hard tissues and soft tissues. There are many methods to prevent the process of corrosion on implant materials such as coating with bioceramic materials and modify the implant surface with surface modification techniques. However, until now there is still no gold standard to overcome this problem and it is remain in researching process. Thus, the aim of this research is to investigate the potential and economical surface modification method to reduce the corrosion effects on Cobalt-Chromium-Molybdenum (Co-Cr-Mo) based alloy when insert in human body. The thermal oxidation process was selected to treat Co-Cr-Mo surface substrate. Firstly, Co-Cr-Mo alloy was heated in muffle furnace at constant temperature of 850°C with different duration of heating such as 3 hours and 6 hours in order to analyze the formation of oxide layer. The corrosion behaviours of untreated sample and oxidized sample were investigated utilizing potentiodynamic polarization tests in simulated body fluids (SBF). The Vickers hardness after corrosion testing was measured in order to evaluate the effect of thermal oxidation in reducing corrosion rate. Based on the results obtained it is clearly showed that substrates undergone thermal oxidation with 6 hours duration time performed better than 3 hours duration, with the hardness value 832.2HV vs. 588HV respectively. Dense oxide layer and uniform thickness formed on the oxidized substrates able to help in reducing the corrosion effects on Co-Cr-Mo alloy without degraded its excellent mechanical properties. The microstructures of oxidized substrates before and after corrosion test were also analyzed using FESEM images for better observations. It was determined that corrosion resistance of Co-Cr-Mo substrate can be increased with oxide layer formed on the alloys using thermal oxidation process.